Spiritual Pilgrimage Through Virtual Reality (VR): Transforming Islamic Religious Education in Madrasahs - Aryati, Aziza; Jamrizal, Jamrizal; Anwar, Khairul; Zulkarnain, Zulkarnain; M, Zaharuddin; Firman, Arham Junaidi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The use of virtual reality (VR) technology in Islamic Religious Education learning in schools has become an interesting topic to improve students’ understanding of religious concepts. This study explores the impact of virtual reality (VR) technology in simulating religious pilgrimage on students’ understanding of religious concepts and teachers’ perceptions. The research conducted used a case study design with a qualitative approach. The research setting was purposively selected at Madrasah Tsanawiyah Negeri (MTsN) 1 Kota Bengkulu. The subjects in this study were Islamic Religious Education teachers and students. The data in this study were collected through observation, interviews, and documentation. Data validity testing in this study was carried out using the triangulation test method. Data analysis in this study adopted a descriptive approach involving several stages, namely data condensation, data presentation, and data conclusion drawing and verification. The results showed: that first, there was a positive acceptance from students towards using Virtual Reality (VR) technology in simulating religious pilgrimage, with many students feeling an enchanting and immersive experience. Second, VR plays a significant role in improving students’ understanding of religious concepts, especially in understanding the historical context and spiritual meaning of holy places. Third, Islamic religious education teachers have a positive perception of the use of VR in learning. The teachers see VR as a tool for increasing student engagement and expanding the learning experience.